A meteorological database for next–generation dispersion models, and a Lagrangian particle model based on kinematic simulation theory. (4th August 2014) - Reimer, E.; Scherer, B.; Klug, W.; Yamartino, R.J.
The database system supports small to regional scale air pollution analysis and dispersion modelling. It provides a three–dimensional and time dependent description of relevant meteorological scalar and vector quantities, and also trajectories and meteorological input data for commonly used dispersion models for local and regional applications. The data are visualized on a standard PC with software provided. The system contains the following modules: a statistical I/O–analysis, a boundary layer model, a short–term regional–scale forecast model (in preparation), a trajectory processor, a non–hydrostatic meteorological local model and interfaces for a variety of transport and dispersion models. Station data and gridded data are archived. Postprocessors extract archived data and process time series, profiles, subregions grid, etc., as required. The new Lagrangian particle model (LPM) uses kinematic simulation theory. It calculates snapshots of concentrations rather than ensemble mean values. It can also directly provide higher moments of concentrations, C n (t), and is applicable for odour problems as well.